Supplement Extending Modules - M.Yaseen, Sahira; Mamoon Tawfeek, Mustafa (Iraqi Journal of Science, 2023)
In this note we consider a generalization of the notion of extending modules namely supplement extending modules. And study the relation between extending and supplement extending modules. And some properties of supplement extending. And we proved the direct summand of supplement extending module is supplement extending, and the converse is true when the module is distributive. Also we study when the direct sum of supplement extending modules is supplement extending.